Pembuatan Game “Snake & Ladder Dungeon” dengan Fitur Virtual Reality - Jonathan Putra Sugito; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
E-commerce is an example among applications which provide services for the user that really popular these days. For example is online shop, it help and give strong impact to the market economic, but unfortunately e-commerce is only developed no more than a sole reason for trading company or online shop itself, and not for other purpose like apps that provide services for a lot of persons that really need it, like in department store. There is a lot of issues which usually visitors do not realize until the transaction is underway in department store, for example is a long queue, hard to find a store which location is not strategic, hard to find a wanted product that make visitors often canceled their intention to shop. This paper offering solution for the problems by creating an e-commerce application named ITEMS. ITEMS made based by web and android. With the apps, user may see the shop list, shop location, catalogue, receive notification(s) for event or sale information, also order product(s) and pay then take it after validation with QR Code. Thus with the solution, the visitors of department store be expected to feel the services provided by the system. So in the end the visitors that use the apps may enjoy the existing service and hopefuly transactions made in department store can multiply